124k views
5 votes
Is each expression equivalent to - 2.7 + (- 3.1)A. -2.7 - 3.1B. -2.7 + (-3) + (-0.1)C. -2 + ( -0.7) + (-3) + (-0.1)D. -2 + 0.7+ ( -3.1)

User Bobby B
by
5.5k points

1 Answer

5 votes

We have the next expression


-2.7+(-3.1)

For A.


\begin{gathered} -2.7+(-3.1)=-2.7-3.1 \\ -2.7-3.1=-2.7-3.1 \\ 0=0 \end{gathered}

This expression is equivalent

For B.


\begin{gathered} -2.7+(-3.1)=-2.7+-3+-0.1 \\ -2.7-3.1=-2.7+-3.1 \\ 0=0 \end{gathered}

This expression is equivalent

For C.


\begin{gathered} -2.7+(-3.1)=-2+-0.7+-3+-0.1 \\ -2.7-3.1=-2.7-3.1 \\ 0=0 \end{gathered}

This expression is equivalent

For D,


\begin{gathered} 2.7+(-3.1)=-2+0.7+(-3.1) \\ 2.7+-3.1=-1.3-3.1 \end{gathered}

The expression is not equivalent

User Gopakumar N G
by
4.7k points